1994
DOI: 10.1083/jcb.125.3.517
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome condensation and sister chromatid pairing in budding yeast.

Abstract: Abstract. We have developed a fluorescent in situ hybridization (FISH) method to examine the structure of both natural chromosomes and small artificial chromosomes during the mitotic cycle of budding yeast. Our results suggest that the pairing of sister chromatids: (a) occurs near the centromere and at multiple places along the chromosome arm as has been observed in other eukaryotic cells; (b) is maintained in the absence of catenation between sister DNA molecules; and (c) is independent of large blocks of rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
424
2

Year Published

1995
1995
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(451 citation statements)
references
References 72 publications
25
424
2
Order By: Relevance
“…21 Because sister chromatid cohesion is present from S phase through metaphase, each mitotic cell contains one fluorescent signal, whereas cells with precociously separated sisters contain two signals. 22 Cells were grown logarithmically and arrested in G 2 /M with nocoda�ole or in G 1 with a-factor. The number of GFP spots per cell was then determined (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…21 Because sister chromatid cohesion is present from S phase through metaphase, each mitotic cell contains one fluorescent signal, whereas cells with precociously separated sisters contain two signals. 22 Cells were grown logarithmically and arrested in G 2 /M with nocoda�ole or in G 1 with a-factor. The number of GFP spots per cell was then determined (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although analysis of the rDNA locus has proven to be a valuable approach, other regions of the genome have been largely neglected. Only a few studies have correlated rDNA condensation to condensation of chromosome regions that are not highly repetitive (Guacci et al, 1994;Lavoie et al, 2000). These studies observed condensation of chromosome XVI using FISH probes 145 kb and/or 255 kb apart.…”
Section: Introductionmentioning
confidence: 99%
“…However, several indirect methods to visualize chromosomes have been developed (reviewed in Loidl, 2003). Visualization of chromosome condensation using fluorescent in situ hybridization (FISH) in budding yeast revealed that highly repetitive rDNA sequences become compact during mitosis (Guacci et al, 1994) and hence this locus became the paradigm to study the process of condensation in yeast. FISH analysis of the rDNA locus revealed that this region of the genome undergoes dramatic structural changes through the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
“…37 The linear chromosome compaction ratio in interphase falls between 70-100 in both yeast 32 and mammalian cells. 38,39 For mitotic chromosomes this number is estimated to be 3,000-2,00,000 in vertebrates [39][40][41] but only 140 in S. cerevisiae 32 and 700 in S. pombe. 42 Thus, the degree of chromosome compaction in mitosis compared to interphase rises dramatically in higher eukaryotes.…”
Section: Regulation Of Chromosome Segregation In Anaphasementioning
confidence: 99%
“…Although human cells deficient of anaphase A are able to separate condensation in mitosis is only marginal in yeast cells and the chromosomes still occupy relatively large space in the nucleus compared to the size of the metaphase spindle. [31][32][33] Thus, depolymerization of the short kMTs is not effective in assisting chromosome segregation and separation of the chromosome arms is only achieved after the spindle poles move apart (Fig. 1B).…”
Section: Contribution Of Anaphase a And B To Chromosome Segregation Imentioning
confidence: 99%